Description of Cadet Sea Practice Experience in Mental Health Review at Maritime Campus X - Zuhriyah, Fitri; Huda, Samsul; Sari, Latifa Ika; Susanti, Eka; Winta, Mulya Virgonita I; Pratiwi, Margaretha Maria Shinta (Jurnal Angkutan Laut dan Kepelabuhanan, 2024)
Various environmental, organizational, cultural, physical, and psychosocial stressors can arise independently or simultaneously in cadets carrying out sea practices. However, stress is not always interpreted negatively. This research aims to explore cadets' marine practice experiences from a mental health perspective, specifically how cadets interpret their experiences when sailing for the first time and facing the dynamics and complexity of challenges during sea practice. This research uses a combination of quantitative and qualitative methods. The quantitative method involved distributing questionnaires with open-ended questions to 101 cadets who had just completed their marine practicals. This was followed by qualitative methods, which included in-depth interviews with five cadets who indicated their willingness to be interviewed. The collected data were then analyzed and categorized based on theoretical studies and presented in tables or diagrams accompanied by a narrative. The research found that cadets view the ship's environment as a new and challenging one. The main problem faced by cadets is adjusting to this new environment. In this adjustment process, cadets must manage their time well to balance personal needs with the need to study or work. Maintaining a harmonious relationship between mind and body, as well as connecting with their experiences, indicates a healthy mental condition. The results of the research indicate that cadets' ability to view stressful situations as challenges, involving commitment and self-control along with social support, can lead to positive attachment. This attachment is meaningful for the job satisfaction cadets experience in carrying out sea practices.